2019
DOI: 10.1177/1049909119832819
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Educational Needs in Managing Complex Pain in Cancer Populations: Evaluation of APAM: An Online Educational Intervention for Nurses

Abstract: Context: Cancer-related pain is associated with significant suffering and is one of the most challenging symptoms to manage. Studies indicate that front-line clinicians often lack the knowledge on best practices in cancer pain management. Objectives: The current project, a quality improvement (QI) initiative, evaluated the outcome of an online educational intervention for nurses on complex cancer pain management. Methods: An online 7-module educational intervention, Advanced Pain Assessment and Management, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“… 25 Leung et al used mixed methods modeling. 26 None conducted item or factor analysis of their questionnaire to assess the discriminating value of items, their match with a hypothesized underlying construct or mapping onto meaningful factors. In our study, for example, this was particularly useful since we saw that our question items did not map clearly to our first list of 6 hypothesized factors, but rather to 3 different ones.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Leung et al used mixed methods modeling. 26 None conducted item or factor analysis of their questionnaire to assess the discriminating value of items, their match with a hypothesized underlying construct or mapping onto meaningful factors. In our study, for example, this was particularly useful since we saw that our question items did not map clearly to our first list of 6 hypothesized factors, but rather to 3 different ones.…”
Section: Discussionmentioning
confidence: 99%
“…21 For cancer pain education, Leung YW and colleagues showed that a facilitator-led online educational intervention can significantly enhance not only knowledge and confidence but also clinical skills in nurses. 22 Three components of our e-learning modules could explain our successful outcomes, including 1) an appropriate learning technique (e-CBL) and material that included wellselected cases and teaching materials, 2) appropriate active tools to increase student engagement such as quizzes in each module, and 3) the flexibility of e-learning that allowed students to learn at their own pace and at convenient times.…”
Section: Discussionmentioning
confidence: 99%
“… 21 For cancer pain education, Leung YW and colleagues showed that a facilitator-led online educational intervention can significantly enhance not only knowledge and confidence but also clinical skills in nurses. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Estes serviram como base para promover reflexões e o pensamento crítico, conforme apresentado nos estudos A2, A3, A4, A5, A7 e A8. Ressalta-se que o uso de simulações virtuais permite ao cursista aproximar-se de cenários mais próximos da realidade, e consequentemente, propicia uma participação ativa no desenvolvimento de competências e de raciocínio para as tomadas de decisão (Leung, et al, 2019;Magalhães, Chaves & Queiroz, 2018;Tomazini, et al, 2018;Melo, Enders & Basto, 2018).…”
Section: Discussionunclassified